Analysis of the Stages of Guidance, Counseling, and Educational Communication as an Educational Intervention Process in Schools - Zahra Maknuna; Ristania Rahayu (Program Studi Bimbingan dan Konseling Islam, 2026)
This study analyzes the stages of guidance, counseling, and educational communication as an integrated process of educational intervention in schools. It is motivated by the increasing complexity of students’ psychosocial problems such as low learning motivation, peer conflict, academic anxiety, and bullying which are often addressed in fragmented and reactive ways. Previous studies tend to examine guidance, counseling, and educational communication separately, resulting in a lack of a comprehensive framework for systematic intervention. Therefore, this study aims to conceptually integrate these three domains into a unified educational intervention process. This research employs a qualitative approach using library research, with data collected from relevant academic literature and analyzed through content analysis. The findings indicate that guidance, counseling, and educational communication share a similar processual structure, including problem identification, diagnosis, intervention planning, implementation, interaction, evaluation, and follow-up. Their integration forms a holistic intervention model that is preventive, curative, and developmental. Educational communication plays a central role as a connecting medium that ensures effective interaction and meaningful behavioral change. This study highlights the importance of an integrative approach to strengthen the role of schools as systematic, humanistic, and responsive educational intervention spaces.